Koncepcja wartości dla klienta - Łada, Monika (The concept of value for customer, 2008)
The growing focus on customers' needs seems to be one of the main trends in contemporary management accounting. The aim of the paper is to present the concept of value for customer. The methods of the measurement of value for customer are discussed. Stakeholder theory is used as a theoretical framework explaining the growing focus of management accounting on customers' needs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 263-270